A plethora of laboratory protocols for vitamin D receptor (VDR) gene variants detection: a systematic review of associations with hypertensive disorders of pregnancy - Ibrahim, Yakubu; Basri, Nurul Iftida; Mohd Jamil, Amilia Afzan; Nordin, Norshariza (BioMed Central, 2025)
Introduction: Genetic variations in the vitamin D receptor (VDR) gene have been inconsistently linked to hypertensive disorder of pregnancy (HDP) across different populations. This systematic review aims to evaluate the laboratory protocols of VDR detection and association with HDP. Methods: We performed a systematic review using the Preferred Reporting Items for Systematic Review and Meta-analysis (PRISMA) guideline and conducted an article search using the Web of Science, PubMed, Scopus, EBSCOhost (MEDLINE and CINAHL) databases. We included all studies involving one or more of the major VDR gene variants (FokI, BsmI, ApaI, and TaqI) and association with HDP. Results: Of the 9 studies evaluated, 6 (67%) studies were reported from Asia, 2 (22%) from Europe, and 1 (11%) from Latin America. Our analysis of VDR variant detection protocols revealed that approximately 6 (67%) studies used polymerase chain reaction restriction fragment length polymorphism (PCR–RFLP), of which 3 (33%) reported a significant association with FokI variant. Two (22%) of studies used TaqMan PCR and found an association with FokI variant. Only 1 (11%) study utilised allele-specific PCR (AS-PCR) for ApaI variant genotyping. For association analysis of the variants with HDP in populations, 4 studies (44%) reported an association with FokI variant in Asians. Two studies (22%) reported BsmI variant in Caucasians. TaqI variant was not associated with HDP in all the populations studied. Conclusions: Our findings suggest an association between VDR genetic variation and HDP across different populations. To enhance consistency in these associations, future studies should use reliable detection methods and strict adherence to quality control measures. This could help in the identification of population-specific biomarkers, prevalent variants, and support personalized management strategies to reduce maternal morbidity and mortality related to HDP.